Mathematical model showing preventive measure as a key to reducing Coronavirus disease (COVID-19) spread - Okoye, C.; Okofu, M.B.; Nubila, N.K.; Ejikeme , C.L.; Agbebaku, D.F. (International Journal of Mathematical Analysis and Modelling, 2024)
A set of non-linear Mathematical equations of COVID-19 model, presented in a ﬂow diagram was proposed to study and ascertain the impact of preventive measures (self isolation and social distancing) to curtailing the spread of the disease. To this eﬀect, we computed the threshold quantity Reff (Eﬀective Reproduction Number), carried out the stability analysis on the equilibrium points obtained using Jacobian technique (Eigenvalue approach), Castilo-Chavez method and a suitable Lyapunov function. We discovered that the Disease Free equilibrium point failed the long term test whereas the Endemic Equilibrium was globally asymptotically stable, thus implying that the COVID-19 spread could be curtailed or curbed in the presence of preventive measures (self isolation and social distancing) as advocated.